Effect of folding factors in rescuing unstable heterologous lipase B to enhance its overexpression in the periplasm of Escherichia coli - Xu, Y. L.; Lewis, D.; Chou, C. P. (Applied Microbiology and Biotechnology, 2008)
Functional expression of recombinant Pseudozyma antarctica lipase B (PalB) in Escherichia coli was explored. While PalB was stably expressed in the cytoplasm, most of the expressed gene product aggregated in cells as inactive inclusion bodies. In contrast, PalB was extremely unstable when expressed in the periplasm, also leading to poor expression performance. Such unstable PalB can be rescued by coexpression of several periplasmic folding factors, such as DegP, FkpA, DsbA, and DsbC but not cytoplasmic ones. As a result, the performance for functional PalB expression in the periplasm was significantly improved. To our knowledge, this is the first report demonstrating the use of folding factors to rescue the extremely unstable gene product that is otherwise completely degradable.